2023
DOI: 10.3390/molecules28062476
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazole—An Antifungal Compound Derived from Medicinal Mushroom Ganoderma lucidum against Mango Anthracnose Pathogen Colletotrichum gloeosporioides (Penz and (Sacc.))

Abstract: The present investigation is focused on exploring the possibilities of identifying biomolecules from the fruiting body of the medicinal mushroom Ganoderma lucidum against the mango anthracnose pathogen Colletotrichum gloeosporioides. The fruiting body (cap and stipe portion) of G. lucidum extracted with ethyl acetate solvent at a maximum inhibitory concentration of 1 percent exhibited the maximum mycelial growth inhibition of C. gloeosporioides with 70.10 percent and 40.77 percent, respectively. Furthermore, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…37,38 Plant organic heterocyclic compounds are another kind of secondary metabolite that exhibit antimicrobial activity. 39,40 In this study, metabolomic analysis revealed that the levels of 10 organic heterocyclic compounds and 4 phenylpropanoids were significantly increased in ΔVdOrlp-infected plants than in wild-type plants. Gayoso et al showed that the levels of phenylpropanoid metabolic products, including ferulic acid, vanillin, and p-coumaric acid, were significantly increased in tomato resistant to V. dahliae after fungal infection.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…37,38 Plant organic heterocyclic compounds are another kind of secondary metabolite that exhibit antimicrobial activity. 39,40 In this study, metabolomic analysis revealed that the levels of 10 organic heterocyclic compounds and 4 phenylpropanoids were significantly increased in ΔVdOrlp-infected plants than in wild-type plants. Gayoso et al showed that the levels of phenylpropanoid metabolic products, including ferulic acid, vanillin, and p-coumaric acid, were significantly increased in tomato resistant to V. dahliae after fungal infection.…”
Section: Discussionmentioning
confidence: 58%
“…This adaptation increases the host’s resilience to changes in external environments. , The inhibitory effects of phenylpropanoids, such as caffeic acid, ferulic acid, naringin, and quercetin, on V. dahliae have been observed. , Plant organic heterocyclic compounds are another kind of secondary metabolite that exhibit antimicrobial activity. , In this study, metabolomic analysis revealed that the levels of 10 organic heterocyclic compounds and 4 phenylpropanoids were significantly increased in Δ VdOrlp -infected plants than in wild-type plants. Gayoso et al showed that the levels of phenylpropanoid metabolic products, including ferulic acid, vanillin, and p -coumaric acid, were significantly increased in tomato resistant to V.…”
Section: Discussionmentioning
confidence: 62%
“…This extract exhibited potent antimicrobial properties toward different human pathogenic microorganisms, including Escherichia coli, Staphylococcus aureus, and Epidermophyton floccosum (dermatophyte). A recent study was designed to evaluate the antifungal effectiveness of G. lucidum against Colletotrichum gloeosporioides, which causes mango anthracnose disease [130]. After being extracted from the fruiting body of G. lucidum using an ethyl acetate solvent, the organic component benzothiazole (50 ppm) demonstrated inhibition of the mycelial growth of C. gloeosporioides.…”
Section: Antimicrobial Activities Of Mushroomsmentioning
confidence: 99%
“…A recent study was designed to evaluate the antifungal effectiveness of G . lucidum against Colletotrichum gloeosporioides , which causes mango anthracnose disease [130]. After being extracted from the fruiting body of G. lucidum using an ethyl acetate solvent, the organic component benzothiazole (50 ppm) demonstrated inhibition of the mycelial growth of C .…”
Section: Antimicrobial Activities Of Mushroomsmentioning
confidence: 99%